Left sided Amyand hernia – A case report. (July 2022) - Joshi, Jayateertha; Mallik, Esha; Ahmed, Talha; Bhat, Rahul; Varghese, George M.
Abstract: Introduction: Amyand hernia is a clinical condition wherein content of the inguinal hernial sac is formed by the vermiform appendix. Case presentation: 1 year 3-month-old male child presented to our OPD with an irreducible left inguinal hernia for which he was taken up for an emergency herniotomy. The terminal ileum, caecum and appendix were found to be the contents of the hernial sac. Discussion: As the appendix is anatomically located on the right, Amyand hernia more commonly occurs on the right, however its occurrence on the left, is a rare event and is usually associated with congenital anomalies like Intestinal malrotation, Situs inversus and mobile caecum. Conclusion: Amyand hernia presenting on the left is extremely rare and high index of clinical suspicion is required to manage such patients. We report one such rare case of a Left sided Amyand hernia in a young child. Highlights: Amyand hernia is the presence of appendix in the hernial sac. Although more common on the right, it may rarely present on the left side. Situs invertus, Malrotation, and Mobile caecum are common causes of left sided Amyand hernia and thus need to be ruled out. High index of clinical suspicion is required as a diagnosis of Amyand hernia is generally made intra-operatively. Standard management is based on Losanoff and Basson's criteria, however it can be individualized as seen in our case.